\(\dfrac{x+3}{2}=\dfrac{x-3}{5}\)
\(\Rightarrow5\left(x+3\right)=2\left(x-3\right)\)
\(\Rightarrow5x+15=2x-6\)
\(\Rightarrow5x-2x=-15-6\)
\(\Rightarrow3x=-21\)
\(\Rightarrow x=-7.\)
Đúng 0
Bình luận (0)
Ta có : \(\dfrac{x+3}{2}=\dfrac{x-3}{5}\)
\(\Leftrightarrow5\left(x+3\right)=2\left(x-3\right)\)
\(\Leftrightarrow5x+15=2x-6\)
\(\Leftrightarrow3x=-21\Leftrightarrow x=-7\)
Vậy x = -7.
bài này còn 1 cách giải nữa nhé bạn !!!
tik mik nha !!!
Đúng 0
Bình luận (0)
\(\dfrac{x+3}{2}=\dfrac{x-3}{5}\)
\(\Rightarrow5\left(x+3\right)=2\left(x-3\right)\)
\(\Rightarrow5x+15=2x-6\)
\(\Rightarrow5x+15+6=2x\)
\(\Rightarrow5x+21=2x\)
\(\Rightarrow-3x=21\)
\(\Rightarrow x=-7\)
Đúng 0
Bình luận (0)